Performance analysis of Double-Ellipse Algorithm for QAM equalization and phase recovery - Chanmanon S. (2014)
This paper presents the performance analysis of new algorithm, called Double-Ellipse Algorithm (DEA), for blind equalization and carrier phase recovery of QAM and cross-QAM signal constellations. The zero-error contour of this algorithm is in the shape of two superimposed ellipses along vertical and horizontal axes. This algorithm combines the benefits of two well-known blind equalization algorithms, the Constant Modulus Algorithm (CMA) and the Reduced Constellation Algorithm (RCA). © 2006 IEEE.